Father André Scrima - A New Kind of Fool for Christ - Vasileanu, Marius (Review of ecumenical studies, 2020)
The complex and often puzzling personality of Father André Scrima was misapprehended for a long time. This article discusses the reasons for such a misapprehension and others some possible explanations for his paradoxical behaviour. An overview of the reception of Father Scrima's life and works shows a dynamic at work that can only generate optimism. His participation in the Burning Bush group at the Antim monastery in Bucharest was one of the most important formative experiences, where a wide cultural and scientific perspective was fused with an in-depth religious experience. Father Scrima may be better understood if we consider him the first of a new kind of fools for Christ, a kind that is well-equipped to face the challenges of tomorrow.